1996
DOI: 10.1172/jci118987
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of calcium-sensing receptor mutations expressed in human embryonic kidney cells.

Abstract: The calcium-sensing receptor (CaR) is a G-protein-coupled receptor that plays a key role in extracellular calcium ion homeostasis. We have engineered 11 CaR mutants that have been described in the disorders familial benign hypercalcemia (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
135
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(150 citation statements)
references
References 33 publications
15
135
0
Order By: Relevance
“…The Thr54Met, Leu135Gln, and Ile200del loss‐of‐function GNA11 mutations are all associated with a mild FHH phenotype characterized by serum adjusted‐calcium concentrations <2.80 mmol/L, and these clinical findings are in keeping with our in vitro studies that have shown FHH2‐associated mutations to induce only minor disturbances of CaSR signal transduction 11. Indeed, the FHH2 mutants were associated with around a 30% increase in the EC 50 values of HEK293‐CaSR cells used in this study, whereas CaSR mutations leading to FHH1 generally cause a >50% increase in the EC 50 value 3, 27. The milder shift in the Ca 2+ o set point of cells expressing FHH2‐associated Gα 11 mutants indicates that the CaSR may promote Ca 2+ i signaling by Gα 11 ‐independent mechanisms, such as via the related Gα q protein.…”
Section: Discussionsupporting
confidence: 89%
“…The Thr54Met, Leu135Gln, and Ile200del loss‐of‐function GNA11 mutations are all associated with a mild FHH phenotype characterized by serum adjusted‐calcium concentrations <2.80 mmol/L, and these clinical findings are in keeping with our in vitro studies that have shown FHH2‐associated mutations to induce only minor disturbances of CaSR signal transduction 11. Indeed, the FHH2 mutants were associated with around a 30% increase in the EC 50 values of HEK293‐CaSR cells used in this study, whereas CaSR mutations leading to FHH1 generally cause a >50% increase in the EC 50 value 3, 27. The milder shift in the Ca 2+ o set point of cells expressing FHH2‐associated Gα 11 mutants indicates that the CaSR may promote Ca 2+ i signaling by Gα 11 ‐independent mechanisms, such as via the related Gα q protein.…”
Section: Discussionsupporting
confidence: 89%
“…receptors with impaired glycosylation or disulfide bond formation are retained in the ER, resulting in reduced cell surface expression and/or total protein abundance (23,30,31). Biochemical studies on loss-or gain-of-function CaR mutants identified in patients suggest that signaling changes may result from differences in cell surface expression (30,32,33). In the present study, we asked whether there is a conformational or functional checkpoint in the biogenesis of CaR using several complementary strategies.…”
Section: Discussionmentioning
confidence: 98%
“…The changes in intracellular Ca 2ϩ levels were expressed as a normalized response. The magnitude of the transient response peak after an individual stimulus was added to the sum of the counts from the previous stimulus and expressed as a proportion of the total counts in the concentration-response curves, as described by Pearce et al (18). Individual EC 50 values (the effective concentration of extracellular Ca 2ϩ giving half of the maximal response) for each incremental, normalized concentration-response curve were plotted using the Sigma Plot software (SPSS, Chicago, IL).…”
Section: Measurement Of Intracellular Ca 2ϩ By Fluorimetry In Individmentioning
confidence: 99%